Pengaruh Waktu dan Temperatur Larutan Terhadap Ketebalan dan Kekerasan Permukaan Lapisan Hasil Elektroplating Kuningan pada Baja - Yuli Yetri; Ultra Marsedi; Jon Affi; Desmarita Leni (Politeknik Manufaktur Negeri Bangka Belitung, 2020)
Brass electroplating process has been analyzed on the steel surface for the thickness and hardness of the coating. The electroplating process was carried out on low carbon steel ST 37 by varying the time (10 minutes, 15 minutes, 20 minutes and 25 minutes), and the temperature of the solution (40 °C, 45 °C, 50 °C, and 55 °C). To determine the quality of the coating results were observed using a stereo microscope and Vicker hard test equipment to measure the thickness and hardness. The test results show that the increase in time and temperature is proportional to the thickness and hardness value obtained. The lowest average thickness and hardness value was 11,323 ?m 182.4 VHN at 40 °C with 10 minutes coloring time. While the highest average thickness and hardness values were 29.333 ?m and 218.8 VHN were obtained at a temperature of 55 °C for 25 minutes. The observations showed a significant increase in thickness and hardness values after 20 minutes. This shows that the higher the solution temperature, it will reduce the absorption of hydrogen into the sludge resulting in an increase in the surface hardness of the resulting layers due to more sediment attached to the cathode. The increase in time and temperature of the solution given is directly proportional to the thickness and hardness value produced on the metal surface.